Toward Facilitating Team Formation and Communication Through Avatar Based Interaction in Desktop-Based Immersive Virtual Environments - Gomes de Siqueira, Alexandre; Feijóo-García, Pedro Guillermo; Stuart, Jacob; Lok, Benjamin (Frontiers in Virtual Reality, 2021)
Millions of students worldwide have adopted online learning due to the isolation restrictions imposed by the Covid-19 pandemic. In this context, video conferencing platforms have garnered immense popularity as tools for teaching. However, these tools have several limitations compared to real-world encounters, especially in activities involving collaboration and teamwork. A growing number of researchers and educators have turned to avatar-based communication platforms, such as Mozilla Hubs, as alternatives that can complement video conferencing in social and teaching activities. Several previous research efforts have focused on developing tools that implement avatar-based communication systems or have explored creating activities in these 3D virtual spaces, such as poster sessions in scientific conferences or the classroom environment. In this work, we describe our semester-long efforts to develop Mozilla Hubs rooms toward promoting interaction and communication to help students self-form teams in the context of an introductory virtual reality course at the University of Florida. We describe hands-on activities to prepare students to use Mozilla Hubs effectively, including teaching them skills to customize and create avatars. We describe the implementation of three virtual rooms developed based on researchers’ observations and students’ survey responses. By observing students’ behavior and communication patterns in those rooms, we propose a set of guidelines for building virtual rooms that can promote communication, interaction, and teamwork. We discuss the rooms’ design, students’ attendance, and avatar choices. Our findings suggest that highly detailed, small, closed spaces are preferred over large, open spaces with few details when promoting interaction and collaboration among students.